2015
DOI: 10.1080/19368623.2015.955622
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Sustainable Management Between Four- and Five-Star Hotels Regarding the Perceptions of Three-Pillar Sustainability

Abstract: Although there are a wealth of publications about sustainability in tourism destination management literature, the concept has only recently started coming under examination within the area of hospitality management. This article’s main focus is on capturing the perceptions and practices of hotel management in respect to the concept of three-dimensional sustainability. A literature-based self-administered questionnaire was used and 423 hotels participated in the study. Logistic regression was employed in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 139 publications
2
61
1
2
Order By: Relevance
“…Since service quality has a significant effect on guests' satisfaction and retention, as well as on lodgings' financial performance and competitive advantage (Chen and Chen, 2014;Stylos and Vassiliadis, 2015;Wu and Ko, 2013;Yang et al, 2011), the current research study has some key managerial implications for networking hospitality and one-to-two-bedroom Airbnb flats in particular. Hence, in addition to its theoretical importance, this study sought to offer valuable advice to hospitality practitioners interested in Airbnb.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Since service quality has a significant effect on guests' satisfaction and retention, as well as on lodgings' financial performance and competitive advantage (Chen and Chen, 2014;Stylos and Vassiliadis, 2015;Wu and Ko, 2013;Yang et al, 2011), the current research study has some key managerial implications for networking hospitality and one-to-two-bedroom Airbnb flats in particular. Hence, in addition to its theoretical importance, this study sought to offer valuable advice to hospitality practitioners interested in Airbnb.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Kim, Kim, & Lee, 2015). In the papers written by authors who analysed higher quality segments, Calveras (2015) and Stylos and Vassiliadis (2015) found that the higher the number of stars, the greater the involvement of hotels in CSR practices. One of the reasons they used to explain why luxury hotels are more involved in their communities is that they use CSR as a differentiation strategy (Calveras, 2015).…”
Section: Hypothesesmentioning
confidence: 99%
“…Out of the 35 papers found in the literature review, only nine papers included any reference to luxury segments, and only three of these papers included results focused on that segment (Calveras, 2015;Li et al, 2015;Stylos & Vassiliadis, 2015). Other papers made some reference to donations by luxury hotels (C. A.…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations